A novel control scheme for voltage multiplier based X-ray power supply - Shahid, Iqbal; Rosli, Besar; C., Venkataseshaiah (2008)
A dual-mode input voltage modulation (IVM) control scheme for a three-phase ZCS series resonant (SR) inverter fed three-phase voltage multiplier based DC-DC converter for X-ray power generator is proposed. The three-phase ZCS SR inverter is formed by connecting three single-phase ZCS SR inverters in parallel and delaying the gating signals by 120 degrees with respect to each other. It operates at constant frequency & duty ratio. The lower arms of all the three single-phase inverters (i.e. which make three-phase ZCS-SR inverter) are connected to a common holding capacitor CH and the voltage V-H across it, is controlled by a control circuit. At the turn ON of the converter, the control circuit clamp voltage V-H to 0V, causing inverter to see full input voltage and output voltage to rise with maximum speed. As the output voltage reaches 80% of target voltage value, the voltage VH is raised from 0V to (V-H)ref, thereby reducing the effective input voltage to inverter. As a result the rise rate of output voltage slow downs and the over shoot is prevented. Experimental results based on the laboratory scale-down prototype are presented to verify the effectiveness of proposed dual-mode IVM control scheme..